2006
DOI: 10.1128/aac.01582-05
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Determination of the Effects of Antibacterial Agents on Mycoplasma agalactiae , Mycoplasma putrefaciens , Mycoplasma capricolum subsp. capricolum , and Mycoplasma mycoides subsp. mycoides Large Colony Type

Abstract: Flow cytometry together with SYBR green I and propidium iodide was used to study the effects of enrofloxacin, ciprofloxacin, gentamicin, chloramphenicol, oxytetracycline, and tylosin on four mycoplasma species. Inhibition of mycoplasma growth could be detected by as early as 3 h after the start of treatment. The strongest effect was observed with enrofloxacin-and ciprofloxacin-treated cells.Contagious agalactia of small ruminants is a serious disease responsible for causing severe economic losses in goat and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These methods have included broth dilutions, solid agar testing, E-strip testing, and most recently, flow cytometry. 2,6,9,10,15,16,18 The MIC values have been determined for Mycoplasma agalactiae, Mycoplasma hyopneumoniae, Mycoplasma putrefaciens, Mycoplasma capricolum, and Mycoplasma mycoides using a selection of antimicrobials with flow cytometry for one isolate of each. …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These methods have included broth dilutions, solid agar testing, E-strip testing, and most recently, flow cytometry. 2,6,9,10,15,16,18 The MIC values have been determined for Mycoplasma agalactiae, Mycoplasma hyopneumoniae, Mycoplasma putrefaciens, Mycoplasma capricolum, and Mycoplasma mycoides using a selection of antimicrobials with flow cytometry for one isolate of each. …”
mentioning
confidence: 99%
“…Under a light microscope, a small section of the agar was identified that contained less than 5 Mycoplasma colonies and no gross contamination from other bacteria. The section was excised from the agar and placed in PPLO broth a for 48 hr at 37°C and 5% CO 2 . The resulting broth suspension was plated again and the process repeated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Propidium iodide has been widely used for viability determination on the basis that it is excluded by the intact membrane of viable animal cells (Jones and Senft, 1985), bacteria (Assunção et al ., 2006) and fungi including S. cerevisiae (Deere et al ., 1998; Achilles et al ., 2006). On entering the cell, PI binds to nucleic acids and its fluorescence is enhanced and thus cells with damaged membranes (dead) fluoresce red while those with intact membranes (alive) do not.…”
Section: Discussionmentioning
confidence: 99%
“…Growth of Mycoplasma has been determined by color changing units (CCU), measuring a decrease in pH after sufficient growth by a change in color (red to yellow) of the pH indicator ( Stemke and Robertson, 1982 ). In this paper, we have used both CCU and a flow cytometric (FCM) method ( Assunção et al, 2005 , 2006 ) to follow growth of Mycoplasma and its inhibition by plant compounds.…”
Section: Introductionmentioning
confidence: 99%